Effect of Pressure and Time of Blow Pin on Thickness of Abfal Mouth of 125 ml EL Bottle Extrusion Blow Molding Process - Aulia Arifin; Vinan Viyus (Pusat Riset dan Inovasi Nasional, 2024)
PT X produces bottles using extrusion blow molding machines that produce EL 125-ml bottles of polypropylene borealis material. In the production process, there is a process of cutting the remaining material at the mouth of the bottle, called abfal. The separation of the abfal from the bottle mouth is still done manually by the operator before the product enters the quality control camera area. This research is experimental, comparing the pressure parameters and blow pin time with the thickness of the abfal mouth using an optical profile projector measuring instrument. In the variation of pressure parameters to the thickness of the abfal mouth, the thinnest occurred in the variation of blow pin pressure fast 80 kg/cm² and blow pin pressure slow 70 kg/cm² by 0.085 mm, and the size of the thickest abfal mouth occurred in the variation of blow pin pressure fast 60 kg/cm² and blow pin pressure slow 50 kg/cm² by 0.195 mm. In the variation of time parameters to the thickness of the abfal mouth, the thinnest occurred at a blow pin time of 1.4s by 0.085 mm, and the size of the thickest abfal mouth occurred at a blow pin time of 1.2s amounting to 0.195 mm. The results showed that the thickness of the abfal mouth is thinner if the pressure and time of the blow pin are given greater, and vice versa, if the pressure and time of the blow pin are given smaller, then the size of the abfal mouth is thicker